Preparation, characterization, and properties of poly(thioether ether imide)s from isomeric bis(chlorophthalimide)s and 4, 4′‐thiobisbenzenethiol. (10th January 2014) - Liu, Jiangtao; Chen, Guofei; Fang, Xingzhong
<x xml:space="preserve">Abstract</x> A series of isomeric poly(thioether ether imide)s (PTEIs) containing both thioether and ether linkages were prepared by nucleophilic substitution reaction of isomeric bis(chlorophthalimide)s with 4, 4′‐thiobisbenzenethiol. The inherent viscosities of these polymers were in the range of 0.40–0.56 dL/g in m‐cresol at 30°C. The Tg values of PTEIs were 196–236°C; T5% values reached up to 509–529°C in nitrogen and 508–534°C in air, which indicated this kind of polyimide possessed excellent thermal stability. The hydrolytic stability was arranged in the order: a > b > c > d > e, and improved with increasing the content of 3‐substituted phthalimide unit in the polymer backbone. Flexible films could be cast from the polymer solution with a solid content of 10%. The PTEI films exhibited good mechanical properties with tensile strengths of 90–104 MPa, elongations at break of 6.6–7.9%, and tensile moduli of 2.3–2.6 GPa. The minimum complex viscosity of PTEIs c was about 100 Pa·s at 310°C and the minimum melt viscosity of PTEIs (a–e) decreased with increasing the content of unsymmetrical 3, 4′‐substituted phthalimide units. Copyright © 2014 John Wiley & Sons, Ltd.